Histori Bencana dan Penanggulangannya di Indonesia Ditinjau Dari Perspektif Keamanan Nasional - Sugeng Yulianto; Rio Khoirudin Apriyadi; Aprilyanto Aprilyanto; Tri Winugroho; Iko Sarikanti Ponangsera; Wilopo Wilopo (University of Bengkulu, 2021)
[History Of Disasters And The Prevention In Indonesia From A National Security Perspective] The development of disaster studies is currently very fast. Disaster events from year to year are a record as well as data on how disasters are very detrimental to human survival as a history. We need a disaster preparedness in anticipation of disaster management by paying attention to the history of disasters and their countermeasures. The authors are interested in analyzing the data from a national security perspective. The research approach used was a descriptive quantitative approach which aims to analyze and describe the history of disasters and disaster management in Indonesia. Sources of data in this study were secondary data in the form of DesInvertar Indonesia and Indonesian Disaster Risk Index data (IRBI). The data analysis technique used was the quantitative method through univariate analysis of the research variables. This research contributes to the latest knowledge regarding the history of disasters and their countermeasures in Indonesia from a national security perspective. The results showed that the incidence of disasters was increasingly varied which caused losses in society. Disasters that occurred in all regions of Indonesia in the period 1815 to 2019 were dominated by climate-induced disasters such as floods with a total of 10,438 events, landslides totaling 6,050 incidents, 2,124 drought events, and forest and land fires totaling 1,914 events. There is an increasing trend of disaster incidents every year, where the total number of disasters in 1815 amounted to 1 increased to 3,885 incidents in 2019. Maintaining national security through disaster risk management is absolutely necessary for the sovereignty of a country, so that good disaster management is a form of protection for the entire nation from all threats, especially national security threats originating from non-military threats in the disaster aspect.